Potential target-organ protection of mineralocorticoid receptor antagonist in acute kidney disease. Issue 1 (January 2019) - Lin, Yu-Feng; Chen, Likwang; Lin, Shuei-Liong; Yeh, Yu-Chang; Huang, Tao-Min; Chou, Yu-Hsiang; Chang, Fan-Chi; Chen, Yi-Ting; Yang, Shao-Yu; Lai, Tai-Shuan; Wu, Vin-Cent; Chu, Tzong-Shinn; et al.
Abstract : Objectives: Acute kidney disease (AKD), the transition of acute kidney injury to chronic kidney disease, has major clinical significance. Whether mineralocorticoid receptor antagonist will afford target organ protection during this critical stage remains ill-defined. Methods: Using a population-based cohort database from January 1999 to July 2011, we identified 7252 AKD patients with hypertension, of whom 2255 were treated with mineralocorticoid receptor antagonist (user) and 4997 were treated by other antihypertensive medication (nonuser). Outcomes were all-cause mortality, major adverse cardiovascular events (MACE), and long-term dialysis dependence. Results: With median 13.37 months of follow-up (IQR 30.53 months), users had a lower incidence of dialysis dependence than nonusers (138.3/1000 person-years vs. 267.2/1000 person-years). After matching users and nonusers (1 : 1) with mortality as a competing risk, Cox proportional hazards analyses showed that mineralocorticoid receptor antagonist therapy was associated with lower risk of dialysis dependence [subhazard ratio (sHR) = 0.83, 95% confidence interval (CI) 0.74–0.93, P = 0.001] but higher risk of hyperkalemia (sHR 1.15, 95% CI, 1.04–1.26, P = 0.005) compared with nonusers. Nonetheless, the risks for all-cause mortality [adjusted hazard ratio (aHR) 1.07, 95% CI 0.98–1.17, P = 0.109] and MACE (sHR 1.08, 95% CI 0.95–1.23, P = 0.210) were similar. Conclusion: Although carrying the risk of hyperkalemia, mineralocorticoid receptor antagonist therapy is associated with similar risk for incident MACE and death; however, with lower risk of long-term dialysis dependence. Our findings have the potential to provide target-organ protection insights in AKD patients with hypertension. Abstract : Supplemental Digital Content is available in the text